Ḥadīth, piety and law: selected studies. By Christopher Melchert. Atlanta, Georgia: Lockwood Press, 2015. Pp. 359. ISBN: 978-1-937040-49-9. - Jamil, Khairil Husaini (IIUM Press, International Islamic University Malaysia, 2018)
Whilst typical modern discourse on Islam speaks of terms such as traditionalism, secularism, salafism, sufism, liberalism, terrorism, etc, the book under review represents an assiduous venture into the historical formative period of Islamic thought and civilisation where traditional Islamic scriptural sciences were at the peak of attention and formulation. Focusing mostly on the second half of the ninth century, Christopher Melchert, a professor of Arabic and Islamic Studies at Oxford, evinces through this collection of engaging articles his profound sympathy for the prominent Muslim historical figures, who according to the editors of this Lockwood series, belong to various pietistic currents that seemed sceptical of some rationalistic tendencies of the time. As a person who has been observing the traditional, rational and spirito-mystical orientations and dimensions in ḥadīth studies .....